Green Economy Practices: A Service Provider's Perspective in Muarajambi Compund Temple - Johannes; Indah Hoirunnisah; Musnaini (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe green economy practices by service providers in the Muarajambi Temple Complex, including implementation forms, supporting and inhibiting factors, and their impact on tourism sustainability and local communities. The study used a qualitative approach with data collection techniques through interviews, observation, and documentation of tour guides, MSMEs, local transportation providers, parking operators, and area managers. Data analysis was conducted thematically through the stages of data reduction, categorization, data presentation, and drawing conclusions to identify patterns of green economy practices developing in the tourist area. The results show that green economy practices are implemented through reducing plastic use, utilizing local materials, waste management, energy efficiency, and promoting environmentally friendly transportation. The implementation of these practices is supported by business awareness and support from area managers, although still facing obstacles such as limited infrastructure and differences in community awareness levels. These findings indicate that green economy practices contribute to tourism sustainability, business efficiency, and improving the welfare of the surrounding communityThis study aims to describe green economy practices by service providers in the Muarajambi Temple Complex, including implementation forms, supporting and inhibiting factors, and their impact on tourism sustainability and local communities. The study used a qualitative approach with data collection techniques through interviews, observation, and documentation of tour guides, MSMEs, local transportation providers, parking operators, and area managers. Data analysis was conducted thematically through the stages of data reduction, categorization, data presentation, and drawing conclusions to identify patterns of green economy practices developing in the tourist area. The results show that green economy practices are implemented through reducing plastic use, utilizing local materials, waste management, energy efficiency, and promoting environmentally friendly transportation. The implementation of these practices is supported by business awareness and support from area managers, although still facing obstacles such as limited infrastructure and differences in community awareness levels. These findings indicate that green economy practices contribute to tourism sustainability, business efficiency, and improving the welfare of the surrounding community